ANALISIS KUALITAS PELAYANAN PENDIDIKAN TERPADU BERBASIS PONDOK PESANTREN - Ratna Komala Putri; Yusep Budiansyah; Vina Silviani Marinda (UNIVERSITAS 17 AGUSTUS 1945 jAKARTA, 2016)
ABSTRACTThe purpose - to produce a study on the quality of service in Vocational High School Based On Boarding Boarding. Design / methodology / approach - A conceptual framework was developed by analyzing previous studies and synthesize the results related to the quality of services in the service sector. Originality / value - This article contributes to the literature on the concept of quality of care in relation Vocational High School Based On Boarding School, with dimensions Selp-esteem, exeed expectation, empowering, Vision, improve and Care Findings - The paper is that the service quality of service shown by SELP-esteem, exeed expectation, empowering, Vision, improve and Care.Keywords: Service Quality, Vocational High School, Islamic Boarding School.ABSTRAKTujuan